Infraestructuras CrÃticas: Sectores Necesitados De Un Modelo De Ciberseguridad - Said, Carlos Gerardo (European Scientific Journal, ESJ, 2016)
The proposed research aims to address the implementation and management of cyber security practices associated with information technology and operational technology regarding network environments of industrial production (SCADA-ICS). Not intended to replace other activities related to cybersecurity, programs, processes, or approaches that organizations of downstream petroleum and natural gas have implemented or intend to implement, including cybersecurity activities associated with legislation, regulations, policies, private initiatives, or the requirements for the business mission. The guidance in this research program is to complement a comprehensive cybersecurity specific areas and industries of oil and gas.